Phenotypic Analysis of Growth and Morphological Traits in Miniature Breeds of Japanese Indigenous Chickens - Ryoko Ono; Haruka Miyachi; Harui Usui; Rina Oguchi; Kenji Nishimura; Kanna Takahashi; Yuri Yamagishi; Nonoka Kawamura; Remi Matsushita; Tatsuhiko Goto (The Journal of Poultry Science, 2022)
Japanese indigenous chickens include approximately 50 breeds exhibiting various morphological traits, such as a long tail. These genetic resources will be important for revealing the genetic basis of morphological traits in the future. However, little is known about the phenotypic characteristics of each breed during the growth stages. To understand age-dependent changes in growth and morphological traits, we investigated tail length, tail number, body weight, and shank length at several time points using three genetically distinct Japanese indigenous chicken breeds. A total of 155 birds from the Tosa-jidori, Chabo, and Minohikichabo breeds were used for trait measurements from 1 to 36 weeks of age to reveal breed and sex effects. Significant sex differences through the growth stages were observed for all traits except for tail number. Although there were no clear breed differences in tail length traits at the 6- and 20-week stages, Minohikichabo ultimately had a significantly longer tail due to extended tail feather growth at later stages (28 and 36 weeks). By measuring two tail length variables (central and maximum), it was revealed that the shape of the tail feathers varies with the growth stage. Minohikichabo’s tail number was higher than that of Tosa-jidori and Chabo at earlier ages (8 and 16 weeks), which leads to an elegant visual in Minohikichabo. Tosa-jidori’s body weight was higher than that of Chabo and Minohikichabo, whereas the shank lengths of Chabo and Minohikichabo were shorter than those of Tosa-jidori. These differences in body weight and shank length were consistent from the early to late growth stages. These results revealed the age-dependency of growth and morphological trait breed characteristics.